Transforming the Role of Cadres through Infant Massage Training: An Empowerment Innovation for Infant Health in Kadujaya Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Infant massage training is a community-based intervention that aims to improve infant health through empowering village cadres. Infant massage has been shown to have many benefits, such as improving infant sleep quality, accelerating weight gain, reducing stress, and strengthening emotional bonds between infants and parents. However, community understanding of correct infant massage techniques is still limited, especially in rural areas. Village cadres as public health agents have an important role in disseminating this information and skills to mothers in their communities. Therefore, infant massage training for Kadujaya village cadres is a strategic step to improve their competence in performing and teaching infant massage with safe and effective methods. This study used a participatory-based training method that included theory and practice sessions. The theory session covered the benefits of infant massage, basic massage techniques, and safety and contraindication aspects, while the practice session was conducted with direct demonstrations by experienced instructors, followed by independent practice by participants with instructor guidance. The results showed a significant increase in the knowledge and skills of cadres after training, with knowledge scores increasing from an average of 60% before training to 90% after training. In addition, observations showed that 85% of participants were able to perform infant massage with the correct technique after attending the training. With this training, village cadres are expected to be able to implement and disseminate the benefits of infant massage to the community, so that they can contribute to improving infant health as a whole. In the future, periodic monitoring and evaluation are needed to ensure the effectiveness and sustainability of this training program.